Ga-68 DOTATATE PET imaging in the management of head and neck paragangliomas: a potential game changer - Alduraibi, Alaa; Bin Essa, Noora; Alruwaili, Ahmed A.; Bomanji, Jamshed (Frontiers in Oncology, 2025)
BackgroundHead and neck paragangliomas (HNPGs) are rare neuroendocrine tumors originating from neural crest cells, with some exhibiting malignant potential. Traditional imaging modalities, such as magnetic resonance imaging (MRI), often have limitations in detecting multifocal or metastatic disease, driving interest in more sensitive diagnostic approaches like Gallium-68 DOTATATE positron emission tomography/computed tomography (Ga-68 DOTATATE PET/CT).MethodsThis retrospective study aimed to assess the effectiveness of Ga-68 DOTATATE PET/CT in the detection and management of HNPGs. Imaging data from 2015 to 2024 were reviewed, identifying four confirmed cases of HNPG. All patients underwent head and neck MRI and Ga-68 DOTATATE PET/CT scans. Data on imaging findings, treatment history, and clinical outcomes were collected and analyzed to compare the performance of Ga-68 DOTATATE PET/CT with other imaging techniques, including Iodine-123 meta-iodobenzylguanidine (I-123 MIBG) scintigraphy and Fluorine-18 fluorodeoxyglucose (F-18 FDG) PET/CT.ResultsGa-68 DOTATATE PET/CT demonstrated enhanced sensitivity in detecting both primary and metastatic lesions compared to MRI and other imaging modalities. It identified additional lesions not seen on MRI, confirmed local recurrence, and detected unsuspected metastatic sites, influencing clinical management. While Ga-68 DOTATATE PET/CT provided more diagnostic clarity than I-123 MIBG in one case, it also revealed additional metastatic sites in a patient with a succinate dehydrogenase (SDH) gene mutation, which were not detected by F-18 FDG PET/CT.ConclusionGa-68 DOTATATE PET/CT is a valuable imaging tool for evaluating HNPGs, with superior sensitivity in detecting both primary and metastatic lesions compared to conventional imaging. Its diagnostic advantages can significantly impact treatment planning and patient management. Integrating Ga-68 DOTATATE PET/CT into clinical guidelines for HNPG evaluation may enhance diagnostic accuracy. Further research with larger cohorts is warranted to confirm these findings and establish standardized interpretation criteria.